Pengembangan SDM Berbasis Human Capital untuk Meningkatkan Kinerja: Studi Kasus Dinas Pemadam Kebakaran dan Penyelamatan Kota Palopo - Nirmasari, Dian; Mas’ud, Busrin Raihana (Pustaka Peradaban, 2025)
Firefighting services require operational personnel who are skilled and prepared to face high risks in ensuring public safety. This study aims to analyze the potential of human resources (HR), human capital–based development strategies, and their impact on the performance of operational personnel at the Fire and Rescue Department of Palopo City. A descriptive method was employed, utilizing interviews, observations, and documentation with 13 informants, and data validation was conducted through source triangulation. The findings reveal that HR development through education, training, and work motivation enhances technical skills, teamwork ability, and overall effectiveness. However, limited personnel and low participation in training remain significant challenges. These findings reinforce Human Capital Theory while also providing practical insights for local governments in designing training programs, certification, and performance evaluation systems. Furthermore, the study offers a model for HR development in fire departments across other regions with similar characteristics. Pelayanan pemadam kebakaran menuntut tenaga operasional yang terampil dan siap menghadapi risiko tinggi demi keselamatan masyarakat. Penelitian ini bertujuan menganalisis potensi sumber daya manusia (SDM), strategi pengembangan berbasis Human Capital, serta dampaknya terhadap kinerja tenaga operasional di Dinas Pemadam Kebakaran dan Penyelamatan Kota Palopo. Penelitian menggunakan metode deskriptif dengan wawancara, observasi, dan dokumentasi terhadap 13 informan, serta validasi melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa pengembangan SDM melalui pendidikan, pelatihan, dan motivasi kerja mampu meningkatkan keterampilan teknis, kemampuan bekerja sama, dan efektivitas kerja. Namun, keterbatasan jumlah tenaga dan partisipasi pelatihan masih menjadi kendala. Temuan ini memperkuat Human Capital Theory sekaligus memberi dasar praktis bagi pemerintah daerah dalam merancang program pelatihan, sertifikasi, dan evaluasi kinerja, serta dapat dijadikan model pengembangan SDM Damkar di daerah lain dengan kondisi serupa.